PENGARUH KOMUNIKASI INTERPERSONAL DOKTER-PASIEN DAN KUALITAS PELAYANANTERHADAP TINGKAT KEPUASAN PASIEN DI POLIKLINIK RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN - Muhammad Hafidz Riyadi; Rahmi Widyanti; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Background of this study was from several complaints and cases that occur in the hospital there are cases of doctors who make mistakes in diagnosing the disease causing lawsuits. This begins because of obstacles in communication Doctor Patient. Some patients complain about the doctor's services not because of the ability or expertise of the doctor, but because they feel less attention. The purpose of this research is to know the influence of doctor-patient interpersonal communication and quality of service to patient satisfaction level in polyclinic of RSUD Dr. H. Moch. Ansari Saleh. This research method is a quantitative descriptive research that includes nonexperimental research because it does not provide treatment to the subject of research. The design of this study using cross-sectional is a study that studies the relationship between risk factors (independent) with the factor effect (dependent), where the observation or measurement of variables once and simultaneously at the same time. The results showed that the coefficient effect of doctor-patient interpersonal communication (X1) to patient satisfaction (Y) was 0.261. While for the coefficient of influence of service quality (X2) on patient satisfaction (Y) is equal to 0,665. From both variables, it is known that service quality variables have the most dominant influence on patient satisfaction in Polyclinic RSUD Dr. Moch. Anshari Saleh Banjarmasin. From the research results can be seen that the coefficient of determination R2 (R Square) is equal to 0.658 (65.80%). These results indicate that the value influence of doctor-patient interpersonal communication and the quality of service to patient satisfaction in Polyclinic RSUD Dr. Moch. Anshari Saleh Banjarmasin is 65.80%.